Prognostic factors in second-line targeted therapy for metastatic clear-cell renal cell carcinoma after progression on an anti-vascular endothelial growth factor receptor tyrosine kinase inhibitor. (3rd March 2016) - Sacré, Anne; Barthélémy, Philippe; Korenbaum, Clement; Burgy, Mickael; Wolter, Pascal; Dumez, Herlinde; Lerut, Evelyne; Loyson, Tine; Joniau, Steven; Oyen, Raymond; Debruyne, Philip R.; Schöffski, Patrick; et al.
Abstract: Background : About 40% of metastatic clear-cell renal cell carcinoma (m-ccRCC) patients receive a second-line targeted therapy after failure of anti-vascular endothelial growth factor receptor tyrosine kinase inhibitors (anti-VEGFR-TKI). Efficacy of second-line therapy is usually limited and prognostic and predictive factors at the start of second-line therapy are lacking. To identify the subgroup of patients that will benefit from such treatment remains a challenge. Methods : We performed a multi-institutional, retrospective study of patients who received a second-line therapy after progression on an anti-VEGFR-TKI. Univariate and multivariate analyses were performed in order to identify prognostic factors for progressive disease (PD) as best response, progression-free survival (PFS) and overall survival (OS) on second-line therapy. Results : For the whole cohort of 108 patients, mOS from the start of second-line therapy was 8.9 months while mPFS on second-line therapy was 2.8 months. A total of 49/105 (47%) patients had PD, 50/105 (48%) stable disease (SD) and 6/105 (6%) a partial response (PR). On multivariate analysis, the following markers were associated with improved outcome on second-line therapy: a PFS on first-line therapy ≥12 months (HR for PFS: 1.961; p = 0.008) (HR for OS: 1.724; p = 0.037) and Fuhrman grade 1–2 tumors (HR for OS: 2.198; p = 0.007). Markers associated with poorer outcome on second-line therapy were: elevated serum lactate dehydrogenase (LDH) levels (HR for PFS: 0.511; p = 0.04) (HR for OS: 0.392; p = 0.017), low albumin (HR for OS: 0.392; p = 0.01) and elevated corrected calcium levels (HR for OS: 0.416; p = 0.01). The impact on OS of the Memorial Sloan Kettering Cancer Centre (MSKCC) and International Renal Cell Carcinoma Database Consortium (IMDC) prognostic scores as calculated at start of second-line therapy was validated in our patient series. Conclusions : Duration of first-line PFS, Fuhrman grade, serum LDH levels, albumin levels, corrected calcium levels and the MSKCC and IMDC scores calculated at start of second-line therapy are prognostic factors for m-ccRCC patients treated with second-line targeted therapy.